Faculty of Pharmacy briefing on fire safety and demonstration of fire fighting / Tiniati Ahmad and Dr. Gurmeet Kaur Surindar Singh - Ahmad, Tiniati; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On March 2, 2023, the Sub-Occupational Safety and Health Committee (SOSHCo), Faculty of Pharmacy, conducted a briefing on 'Fire Safety and Demonstration of Fire Fighting' at Dewan Kuliah 4, FF4 Building, UiTM Puncak Alam Campus. More than 50 staff members, including academic staff and supporting staff from the Faculty of Pharmacy and Rector's Office, attended the event, which was officiated by the Deputy Dean (Student Affairs), Dr. Aida Azlina Ali.